MINAT BACA MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS NIAS RAYA - Eviratnasari Halawa (Universitas Nias Raya, 2024)
The background of the problem in this study is that students' interest in reading decreased due to the inability to understand what they read and the reading language that did not attract students. Students of the Indonesian Language and Literature Education Study Program prefer to read novels rather than ceta books that are already available in the library. The purpose of this study is to describe the reading interest of Indonesian Language and Literature Education students, Faculty of Teacher Training and Education, Nias Raya University. The results of the study found that those who had an interest in reading Indonesian Language and Literature Education students were 11 people from various semesters, while those who had less interest in reading Indonesian Language and Literature Education students were 5 people. Suggestions in this study are: 1) The need for assistance from lecturers to expedite the learning process and provide exercises to students and provide guidance. This is important to do so that students want to read; 2) Students are expected not only to listen to explanations from lecturers, but should read a lot of books related to literary works in order to better understand what is explained by lecturers;